Comparison the Effectiveness of Chitosanin Blue Crab Shells with Ciprofloxacin to the Development of Eschericia coli - Sari, Novita; Boy, Elman (International Journal of Human and Health Sciences (IJHHS), 2018)
Background: Escherichia coliis a normal intestinal flora that have contributions on the normal functioning of human digestion, but it will turn into a pathogen when it is outside the intestinal tract. E. coli including family Enterobacteriaceae, facultative anaerobic. Characteristics of E. coli is a bacteria gram-negative rod-shaped, motile with flagella or nonmotile, fermentation of glucose, and producing gas. Chitosan has antimicrobial effect against bacteria. Amine moieties of chitosancontent positively charged which is very reactive, and have the ability to bind with the cell walls of bacteria are negative charged. Amine cluster also has a free electron pair, so it was able to attract minerals Ca2+ in the cell walls of bacteria. Objective: to know the comparative effectiveness of chitosanon the shell of a small crab attaching with ciprofloxacin antibiotics against the development of the bacteria E. coli. Methods: this research uses experimental methods. Techniques used in measuring antimicrobial activity is the diffusion disc method. Results: the results showed that the average diameter of the inhibitory zones of chitosanagainst E. coli in a row with a concentration of 4%, 5%, 6%, 7%, and 8% is 14.22 mm, 11.94 mm, 9.18 mm, 11.19 mm, and 8.76 mm. Whereas the average diameter of the inhibitory zones of ciprofloxacin is 42.31 mm. Conclusion: Chitosanon small crab attaching shells with a concentration of the most effective in inhibiting the development of the bacteria E. coli is chitosanwith concentrations of 4% with the average drag zone amounting to 14,22 mm. International Journal of Human and Health Sciences Vol. 02 No. 04 October’18. Page : 217-219